Innovation in forage development: Empirical evidence from Alaba Special District, southern Ethiopia - Shiferaw, A.; Puskur, Ranjitha; Tegegne, Azage; Hoekstra, Dirk (Informa UK Limited, 2011)
Forage development is one of the strategies to address feed scarcity and low livestock productivity in Ethiopia. In line with government strategy, multiple actors took part in a forage development programme for six years (2004–09) in Alaba Special District, in southern Ethiopia. This paper analyses the six-year forage development programme, comparing its two phases, from an innovation systems perspective to identify best practices. The study shows that key forage innovative practices are: targeting innovative forage farmers, developing local forages, establishing private forage sources, forage promotion and diversifying capacity building. These best practices can be scaled up and out to address feed scarcity and increase livestock productivity.